Quantifying Severity of Maltreatment, Adversity, and Trauma From Child Protective Services Case Record Files. Issue 17 (September 2021) - Grasso, Damion J.; DiVietro, Susan; Beebe, Rebecca; Clough, Meghan; Lapidus, Garry
Children referred to child protective services (CPS) for allegations of abuse or neglect often have diverse experiences of maltreatment, adversity, and trauma. Severity of these experiences is associated with greater mental health impairment and increased risk of revictimization and other adversities. Although aspects of these experiences are often captured during CPS investigations and stored in case records as narrative documents, much of this information is underutilized in estimating risk and service planning. The current study extracted case record information from a randomly selected sample of 100 families, with 150 children referred to CPS during a 12-month period. The Yale-Vermont Adversity in Childhood Scale (Y-VACS) was applied to extracted information for quantifying severity of various forms of childhood maltreatment, adversity, and trauma. Study aims were to examine (a) the scope and severity of maltreatment, adversity, and trauma types and their associations; (b) linkages between severity and CPS allegation types and outcomes; and (c) the utility of severity in predicting new allegations of abuse or neglect within 12 months of referral. Results indicated feasibility in quantifying severity of maltreatment and other adversities from case record information and revealed associations between adversity severity and CPS allegation types and outcomes. Severity of psychological intimate partner violence and neglect were predictive of new allegations of abuse or neglect within 12 months of referral. Findings support moving beyond an incident-based CPS strategy to one that better incorporates case record information to assess risk.